Progettare parchi agricoli nei territori intermedi (2015)
In recent years, numerous reflections have pushed on the importance of using agricultural parks to recreate reciprocal relationships between urban and rural realities, through the enhancement of their proximity. The parks can also be an opportunity to experiment with new forms of planning on a territorial scale, oriented towards the construction of unitary and coherent morphological, functional and environmental scenarios. This volume offers a reflection on these issues by sharing the results of a design experience involving the School of Territory studies of Empoli (Degree in Urban and Territory Planning) and the School of territorial engineering of Clermont Ferrand (AgroParisTech ENGREF). The scenarios arising from the reflection synthesize these two approaches, integrating the interpretation of equities with the processes of diagnostic territorial and with the construction of shared territorialities.